2004
DOI: 10.1002/mop.11399
|View full text |Cite
|
Sign up to set email alerts
|

Continuous hybrid approach to the modified resonant frequency calculation for circular microstrip antennas with and without air gaps

Abstract: In this work, a continuous hybrid approach (CHA) to the modified resonant frequency calculation for circular microstrip antennas with and without air gaps is presented. The results obtained by the CHA for different antenna dimensions and modes of resonance are compared with the experimental and theoretical results given in the literature. © 2004 Wiley Periodicals, Inc. Microwave Opt Technol Lett 40: 423–427, 2004; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.11399

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…The average percentage error of theories of Gurel and Yazgan [6 -8] is around 0.36%. The following theory presented by Guha [9], produced from new dynamic permittivity and radius extension formula, results with average percentage value of 0.57 and the recent theory presented by Gunel [10], produced from continuous hybrid algorithm depending on continuous parameter genetic algorithm, results with an average percentage error value of 0.28. In the last column of Table 1, the resonant-frequency results of the present study, f GAY , are shown.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The average percentage error of theories of Gurel and Yazgan [6 -8] is around 0.36%. The following theory presented by Guha [9], produced from new dynamic permittivity and radius extension formula, results with average percentage value of 0.57 and the recent theory presented by Gunel [10], produced from continuous hybrid algorithm depending on continuous parameter genetic algorithm, results with an average percentage error value of 0.28. In the last column of Table 1, the resonant-frequency results of the present study, f GAY , are shown.…”
Section: Resultsmentioning
confidence: 91%
“…Experimental [2] and theoretical [1][2][3][4][5][6][7][8][9][10] [3], Roy and Jecko [4], Guney [5], Gurel and Yazgan [6 -8], Guha [9], Gunel [10], and the present formulation, which are mainly produced from the cavity analysis depending of the usage of effective or dynamic permittivity values combined with effective or physical patch radius values. Average percentage error values are also shown in the same table indicating the accuracy is affected mainly by the gap thickness and the mode numbers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bandwidth of microstrip antenna can be increased by designing the antenna with an air gap [1,4]. In order to obtain tunable characteristics, providing a wider bandwidth at the same time, a simple solution was proposed in the literature [5][6][7][8][9][10]. This was the inclusion of an adjustable air gap between the ground plane and the substrate resulting in a two-layered structure having new resonant frequency value [7].…”
Section: Introductionmentioning
confidence: 99%